Personal Data as an Object of Performance in Digital Contracts: Reconstruction of the Concept of Objects of Contracts in Indonesia - Nur Wakhid; Frida Nurrahma Masturi; Anandyta Nur Khoirunnisa (Greenation Research & Yayasan Global Resarch National, 2026)
Title:Personal Data as an Object of Performance in Digital Contracts: Conceptual Reconstruction of the Object of Obligations in Indonesia. This article examines the research object of personal data within digital obligations that is motivated by the gap between the digital economy reality utilizing personal data as an economic commodity and positive law focusing strictly on protection. The objective is to analyze the qualification of personal data as an object of performance in digital contracts and examine its legal standing as user consideration for platform services. The method used is normative legal research with statute and conceptual approaches. The results show that personal data can be qualified as an object of performance under the Indonesian Law of Obligations based on the Indonesian Civil Code. The performance does not entail an absolute transfer of ownership, but rather the granting of legitimate access and utilization rights. The legal standing of personal data functions as a digital asset forming a non-monetary counter-performance in a reciprocal legal relationship. This study concludes that a conceptual reconstruction of the object of obligations is necessary to accommodate digital economy developments without eliminating the inherent privacy rights of data subjects protected by the Personal Data Protection Law.